2019
DOI: 10.1002/jcp.28671
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA‐155‐5p from PDLSCs regulated Th17/Treg balance by targeting sirtuin‐1 in chronic periodontitis

Abstract: The mechanism of local inflammation and systemic injury in chronic periodontitis is complicated, in which and exosomes play an important role. In our study, we found that T helper cell 17 (Th17)/regulatory T cell (Treg) balance is destabilized in the peripheral blood of patients with periodontitis, with upregulated Th17 or downregulated Treg, respectively. Porphyromonas gingivalis lipopolysaccharide (LPS) was used to simulate the inflammatory microenvironment of chronic periodontitis. The exosomes were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 44 publications
7
82
1
Order By: Relevance
“…Therefore, a transwell indirect co-culture system was employed to mimic cell-to-cell communication. Functions of PDLSCs are affected by inflammatory environment resulted from periodontitis, such as proliferative capacity, osteogenic potential and regulatory ability [27][28][29]. In our study, VEGFA, the vascular specific marker, was up-regulated in PDLSCs derived from periodontitis, suggesting that inflammation might affect the pro-angiogenesis of PDLSCs.…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, a transwell indirect co-culture system was employed to mimic cell-to-cell communication. Functions of PDLSCs are affected by inflammatory environment resulted from periodontitis, such as proliferative capacity, osteogenic potential and regulatory ability [27][28][29]. In our study, VEGFA, the vascular specific marker, was up-regulated in PDLSCs derived from periodontitis, suggesting that inflammation might affect the pro-angiogenesis of PDLSCs.…”
Section: Discussionsupporting
confidence: 48%
“…cells, downregulation pro-inflammatory IL-17, promotion differentiation of Tregs (31,51,74,76,94) (Table 1) and CTLA-4+ Tregs (74), upregulation anti-inflammatory TGF-β, and inhibition aberrant inflammatory responses in stroke (31), type 1 diabetes (51,76), and chronic periodontitis (94). A possible underlying mechanism could be the immune equilibrium controlled by PGE2 and TGF-β (76) signaling pathways or miRNA-155-5p (94) in EVs. A second underlying mechanism could be the induction of phenotypic transition of macrophages into M2 to regulate T cells indirectly by EVs derived from human NSCs (31) ( Table 1).…”
Section: Sc-evs Regulate Th17/treg Balance Such As Inhibition the Difmentioning
confidence: 99%
“…Th17 and Treg cells are two vital lymphocyte subsets with opposing functions [11]. Abnormal ratio of Th17 and Treg have been frequently found to be a key feature of metabolic or immunologic disorder-associated diseases, including several types of chronic inflammations [12,13], allergic diseases [14,15], autoimmune diseases, and cancers [16,17]. A number of studies have shown that gut microbiota is closely associated with the balance of Th17 and Treg.…”
Section: Introductionmentioning
confidence: 99%